2009
DOI: 10.1080/00288330909510009
|View full text |Cite
|
Sign up to set email alerts
|

Variability in trap catches for an American lobster,Homarus americanus, spring fishery

Abstract: At-sea sampling is a common approach used by fisheries scientists to assess changes in fished populations. Traditional sampling programmes focus on short intensive sampling periods by fisheries personnel, although there has been a move to increase temporal sampling frequency within a fishing season by using harvesters. To determine the suitability of these two options, we compared the precision of estimates obtained for the American lobster (Homarus americanus) fishery in the southern Gulf of St. Lawrence, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In contrast, the evidence from our simulations indicated that measuring the entire catch from 10% of fishing days would not provide representative data on the length structure of the commercial catch in this fishery. This is because this sampling program is unlikely to capture the heterogeneity in length structures among different abalone populations, as the catch is sampled from only a small sub-set of the actual number of fishing days (Pennington et al, 2002;Comeau et al, 2009). This finding is consistent with previous studies that demonstrate increased precision and accuracy through sampling more primary units (Pennington and Volstad, 1994;McGarvey and Pennington, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the evidence from our simulations indicated that measuring the entire catch from 10% of fishing days would not provide representative data on the length structure of the commercial catch in this fishery. This is because this sampling program is unlikely to capture the heterogeneity in length structures among different abalone populations, as the catch is sampled from only a small sub-set of the actual number of fishing days (Pennington et al, 2002;Comeau et al, 2009). This finding is consistent with previous studies that demonstrate increased precision and accuracy through sampling more primary units (Pennington and Volstad, 1994;McGarvey and Pennington, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Collection of these fishery-dependent data is typically far less expensive than obtaining fishery-independent information, such as survey measures of abundance (Prince and Hilborn, 1998;Kimura and Somerton, 2006;Kristensen et al, 2006;McGarvey et al, 2008). Cost is an important consideration, particularly where licence or access fees are levied against fishers to recover expenses associated with the management of their fishery, and has led to more adaptive measures being employed to collect relevant data (Hart et al, 2008;Prince et al, 2008;Comeau et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among those factors, different types of fishing strategy such as trap and trawl design are clearly relevant (Comeau et al, 2009). A better understanding of these factors will minimize the risk associated with population estimates from catch data directly from the commercial fishery (Smith and Tremblay, 2003).…”
Section: Differences In Catch Rate Among the Four Traps In The Trawlmentioning
confidence: 99%
“…While the effects of biotic and abiotic factors have been well documented, little research has examined the effects of fishing strategies on catch rates (Miller and Rodger, 1996;Comeau et al, 2009), particularly trap and trawl design. Trap design can vary by size, material, and location of entrances, while trawl design (a trawl is a group of traps connected on a line to a surface buoy; Comeau et al (2009)) includes the number and spacing of traps and the presence of extra buoys (Smith and Tremblay, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation